Functional overreaching during preparation training of elite tennis professionals - Thiel, C.; Vogt, L.; Bürklein, M.; Rosenhagen, A.; Hübscher, M.; Banzer, W. (Journal of Human Kinetics, 2011)
This case study evaluated the response of objective and subjective markers of overreaching to a highly demanding conditioning training mesocycle in elite tennis players to determine 1) whether players would become functionally or non-functionally overreached, and 2) to explore how coherently overreaching markers would respond. Performance, laboratory and cardiac autonomous activity markers were evaluated in three experienced male tennis professionals competing at top 30, top 100 and top 1000 level before and after their strength and conditioning training was increased by 120, 160 and 180%, respectively, for 30 days. Every week, subjective ratings of stress and recovery were evaluated by means of a questionnaire. After 74, 76 and 55 h of training, increases in VO2max (+8, +5 and +18%) and speed strength indices (+9, +23 and +5%) were observed in all players. Changes of maximal heart rate (-5, -6, +4 beats per minute), laboratory markers (e.g. insulin-like growth facto -]26, -17, -9%; free testosterone to cortisol ratio -63, +2, -12%) and cardiac autonomous activity markers (heart rate variability -49, -64, -13%) were variable among the players. Improved performance provides evidence that overreaching was functional in all players. However, several overreaching markers were altered and these alterations were more pronounced in the two top 100 players. The response of overreaching indicators was not coherent.